Enthalpy change in the magnetocaloric effect - Quintero, Mariano Horacio (2012)
-We report a study of the magnetocaloric effect in magnetic systems by extracting the temperature change from the enthalpy difference between the high and the low magnetic field phases. To evaluate this alternative approach, we compare the results extracted from the proposed model with direct measurements of the adiabatic temperature change. Results obtained in the manganite compound Pr0.5Sr0.41Ca0.09MnO3 are used to show that this method is valid and useful to evaluate the magnetocaloric effect in different solid state systems, and to follow the heat dynamic of the system while a magnetic first order phase transition takes place.